Determinan Keputusan Pembelian Produk pada Tiktok Shop Aerostreet - I Kadek Sudiarta; Putu Purnama Dewi (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the determinants of purchase decisions for Aerostreet products on TikTok Shop by focusing on the roles of live streaming and influencers, as well as consumer trust as a mediating variable. The research is motivated by the phenomenon of high Aerostreet sales on TikTok Shop despite consumer complaints regarding product quality, and by previous studies that show inconsistent results regarding the influence of live streaming and influencers on purchase decisions. This research employs a quantitative approach with the TikTok Shop Aerostreet account as the object and involves 160 respondents who have made purchases from the store, selected using purposive sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using SEM-PLS, including outer model testing (validity and reliability) and inner model evaluation (R-square, F-square, Q-square, and hypothesis testing). The results indicate that live streaming and influencers have a positive and significant effect on purchase decisions, and also a positive and significant effect on consumer trust. Consumer trust is likewise shown to have a positive and significant effect on purchase decisions. In addition, consumer trust positively and significantly mediates the relationship between live streaming and purchase decisions, as well as between influencers and purchase decisions on TikTok Shop Aerostreet. These findings confirm that marketing strategies through live streaming and influencers are more effective in driving purchase decisions when they are able to build strong consumer trust.